Biofilms and icaA and icaD genes in coagulase-negative staphylococci isolated from central venous catheters from the intensive care unit of a level III hospital in Lima, Peru - Salazar, María E. (2018)
Objective: To determine the presence of icaA and icaD genes in biofilm-forming coagulase-negative staphylococci (CoNS) isolated from central venous catheters (CVCs) from the intensive care unit of the Hospital Nacional Guillermo Almenara Irigoyen (HNGAI). Materials and methods: One hundred fifty-one (151) CVCs were collected from the HNGAI in Lima. For the microbiological analysis, 30 CVCs were randomly selected for the Maki method and 121 for the Donlan method. A total of 73 CoNS isolates were obtained and their ability to form biofilms was evaluated using Congo red agar (CRA). CRA-positive isolates showed the presence of icaA and icaD genes by polymerase chain reaction (PCR). Results: Out of the 27 CoNS isolated from the external surface of the CVCs, 81 % (22/30) were CRA positive, of which 13.6 % (3/22) presented both genes. Out of the 46 CoNS isolated from the internal surface of the CVCs, 48 % (22/46) were CRA positive, of which 22.7 % (5/22) showed both genes. Conclusions: Thirteen point six percent (13.6 %) and 22.7 % of the biofilm-forming CoNS isolated from the external and internal surfaces of the CVCs, respectively, were carriers of both icaA and icaD genes.